2020
DOI: 10.1097/txd.0000000000001065
|View full text |Cite
|
Sign up to set email alerts
|

Rejection-associated Mitochondrial Impairment After Heart Transplantation

Abstract: Background. Mitochondrial dysfunction is associated with poor allograft prognosis. Mitochondrial-related gene expression (GE) in endomyocardial biopsies (EMBs) could be useful as a nonimmune functional marker of rejection. We hypothesize that acute cardiac allograft rejection is associated with decreased mitochondrial-related GE in EMBs. Methods. We collected 64 routines or clinically indicated EMB from 47 patients after heart transplant. The EMBs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Romero et al . described a decreased activity of mitochondrial‐related genes in ACR 20 . Our results complement these findings and suggest the translation of alterations in mitochondrial gene regulation in functional alterations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Romero et al . described a decreased activity of mitochondrial‐related genes in ACR 20 . Our results complement these findings and suggest the translation of alterations in mitochondrial gene regulation in functional alterations.…”
Section: Discussionsupporting
confidence: 87%
“…[30][31][32] Romero et al described a decreased activity of mitochondrial-related genes in ACR. 20 Our results complement these findings and suggest the translation of alterations in mitochondrial gene regulation in functional alterations. These findings expose mitochondrial dysfunction as a potential therapeutic target in ACR, especially considering promising effects of dietary interventions on mitochondrial bioenergetics.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…16 Gene expression profiling studies have shown that myocardial samples obtained during an episode of rejection have decreased activity of mitochondrial-related genes and increased activity of immune response genes. 17 Chronic tumour necrosis factor-alpha exposure alters mitochondrial function through the activation of nuclear factor-kappa B. 18 Anticardiac antibodies directed against ATP synthase have been reported in end-stage heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, proteomic analysis of allograft tissue identified downregulation of mitochondrial energy generation, particularly TCA enzymes such as aconitate hydrase in ACR 5 . Transcriptomic analysis of rejecting allograft tissue also identified significant disruption of the mitochondria‐related genes implicated in substrate metabolism, energetics, and regulation of oxidative stress 6 . These studies point to a more critical role of the mitochondrion in rejection.…”
mentioning
confidence: 97%